“A problem they don’t even know exists”: Inequality, poverty, and invisible discourses in Teach First New Zealand - Oldham, Sam; Crawford-Garrett, Katherine (Education Policy Analysis Archives, 2019)
This research draws on qualitative data collected in Aotearoa New Zealand over a six-month period to examine the ways in which participants in Teach First New Zealand (TFNZ), an affiliate of Teach for All, discuss issues of poverty and educational underachievement in their teaching contexts. Findings from this study suggest that broad discursive patterns tended to prevail among TFNZ participants interviewed. In discussing issues of poverty and educational underachievement, participants privileged personal responsibility, individual agency, and social mobility as explanatory frameworks. Participants tended to perceive individuals, families, and communities as responsible for their socioeconomic disadvantage, and few were able to articulate more complex understandings. We found that TFNZ participants had little or no direct experience with poverty or educational inequity prior to entering the scheme and had limited understandings of these phenomena. Despite this, participants shared an almost universal belief that education was the primary means by which disadvantage could be overcome, privileging individualist conceptions of complex social phenomena. As Teach for All expands globally, there is need for empirical work documenting how participants articulate their mission of addressing inequity, how these understandings translate into practice, and the ways in which implicit and explicit educational discourses shape their perspectives on students and communities. This work has added importance as Teach for All actors continue to encourage the movement of alumni into policy and leadership.